Urban and regional planning - "Hall, Peter" (London, 1992)
Provides students with an up-to-date introduction to planning and traces the evolution of problems, planning philosophies, techniques and legislation from a historical perspective in order to explain modern planning practices today.
Keywords: Urban planning